Electrolyte tuning in dye-sensitized solar cells with N-heterocyclic carbene (NHC) iron(II) sensitizers - Mariia Karpacheva; Catherine E. Housecroft; Edwin C. Constable (Beilstein Journal of Nanotechnology, 2018)
We demonstrate that the performances of dye-sensitized solar cells (DSCs) sensitized with a previously reported N-heterocyclic carbene iron(II) dye in the presence of chenodeoxycholic acid co-adsorbant, can be considerably improved by altering the composition of the electrolyte while retaining an I−/I3− redox shuttle. Critical factors are the solvent, presence of ionic liquid, and the use of the additives 1-methylbenzimidazole (MBI) and 4-tert-butylpyridine (TBP). For the electrolyte solvent, 3-methoxypropionitrile (MPN) is preferable to acetonitrile, leading to a higher short-circuit current density (JSC) with little change in the open-circuit voltage (VOC). For electrolytes containing MPN, an ionic liquid and MBI (0.5 M), DSC performance depended on the ionic liquid with 1-ethyl-3-methylimidazolium hexafluoridophosphate (EMIMPF) > 1,2-dimethyl-3-propylimidazolium iodide (DMPII) > 1-butyl-3-methylimidazolium iodide (BMII) ≈ 1-butyl-3-methylimidazolium hexafluoridophosphate (BMIMPF). Omitting the MBI leads to a significant improvement in JSC when the ionic liquid is DMPII, BMII or BMIMPF, but with EMIMPF the removal of the MBI additive results in a dramatic decrease in VOC (542 to 42 mV). For electrolytes containing MPN and DMPII, the effects of altering the MBI concentration have also been investigated. Although the addition of TBP improves VOC, it causes significant decreases in JSC. The best performing DSCs with the NHC-iron(II) dye employ an I−/I3−-based electrolyte with MPN as solvent, DMPII ionic liquid (0.6 M) with no or 0.01 M MBI; values of JSC = 2.31 to 2.78 mA cm−2, VOC = 292 to 374 mV have been achieved giving η in the range of 0.47 to 0.57% which represents 7.8 to 9.3% relative to an N719 reference DSC set at 100%. Electrochemical impedance spectroscopy has been used to understand the role of the MBI additive in the electrolytes.